Law Enforcement of the Crime of Money Laundering Against Perpetrators of Mining Without a License in Indonesian Territory - Zudan Arief Fakrulloh; Budi Novianto (Jurnal Indonesia Sosial Sains, 2024)
The purpose of this research is to describe law enforcement arrangements for unlicensed mining actors involved in money laundering crimes. The author uses a normative juridical approach, using primary and secondary data. Data analysis uses qualitative analysis. Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 11 of 2018 concerning Procedures for Granting Areas, Licensing and Reporting to Mineral and Coal Mining Business Activities, in Article 1 paragraph 10 it is stated that the Rock Mining Business Permit Area, referred to as the Rock WIUP, is part from the Batuan WUP which is given to Business Entities, cooperatives and individuals through applications. So, everyone has to go through an application first to get a Mining Business Permit Area (WIUP). In Indonesia, legal regulations regarding the prevention and eradication of money laundering crimes were initially regulated in Law Number 15 of 2002 concerning the Crime of Money Laundering (UUTPPU) which was later revised into Law Number 25 of 2003 and subsequently revoked and replaced by Law- Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. The results show that perpetrators of money laundering crimes are subject to sanctions based on Articles 6, 7, 8, 9, and 10 of Law Number 8 of 2010 concerning Money Laundering Crimes.